Research on the Heavy Gas Action Characteristics of BF Type Double Float Ball Gas Relay Under Transient Oil Flow Impact - Liu, Chengxiang; Zhang, Tengbo; Zhang, Chunhui; Xu, Bo; He, Shixian; Wan, Shuting (Energies (Basel), 2025)
The gas relay is a common non-electric protection device inside transformers, installed on the connecting pipeline between the transformer oil tank and the oil conservator. When the transformer malfunctions and the oil flow value reaches the heavy gas setting value of the gas relay, a heavy gas alarm is triggered. Therefore, accurately analyzing the heavy gas action characteristics and the setting value of the gas relay directly affects the accuracy of the heavy gas alarm. The BF(Bi-Float) type double float ball gas relay uses steady-state oil flow to calibrate the setting values of heavy gas action. In reality, transformer faults cause transient oil flow. To explore the relationship between the oil flow state and gas relay flow velocity setting values, a dynamic model of the heavy gas action process of BF type double float ball gas relay was first established, and the influence of the oil flow state on the gas relay baffle action process was analyzed. Then, a transient oil flow impact test bench was developed to experimentally study the heavy gas action characteristics of gas relays under different intensities of transient oil flow impact. Theoretical and experimental research results indicate that different oil flow impact states have a significant effect on the flow velocity setting values of gas relays. The flow velocity setting value of the BF type double float ball gas relay used in this study under transient oil flow impact is 0.8 m/s, which is lower than its factory flow velocity setting value of 1 m/s. These research results have positive significance for optimizing the performance of gas relays and improving the operational reliability of power transformers.